фото
Объяснение:
2(2x−8)² − 11(2x−8) + 12 = 0
чтобы не возиться со страшными цифрами делаем замену 2x-8=t
2t² - 11t + 12 = 0
D = 11² - 4*2*12 = 121 - 96 = 25
t ₁₂ = (11 +- 5)/4 = 4 3/2
1. t = 4
2x - 8 = 4
2x = 12
x = 6
2. t = 3/2
2x - 8 = 1.5
2x = 9.5
x = 4.75 = 4 3/4 = 19/4
фото
Объяснение:
2(2x−8)² − 11(2x−8) + 12 = 0
чтобы не возиться со страшными цифрами делаем замену 2x-8=t
2t² - 11t + 12 = 0
D = 11² - 4*2*12 = 121 - 96 = 25
t ₁₂ = (11 +- 5)/4 = 4 3/2
1. t = 4
2x - 8 = 4
2x = 12
x = 6
2. t = 3/2
2x - 8 = 1.5
2x = 9.5
x = 4.75 = 4 3/4 = 19/4